Context and Action in the Transformation of the Firm: A Reprise - Pettigrew, Andrew M. (Journal of Management Studies, 2012)
abstractThis article returns to address the strengths and limitations of Pettigrew 1985 and 1987. It then responds to two of the main deficiencies of those publications. These are the failure to link context to process to outcome in those studies and in process scholarship more generally and the limited treatment of the method of process analysis offered by Pettigrew in 1985 and 1987. The article then compares and contrasts the methods of five additional process scholars – Mintzberg, Burgelman, Langley, Van de Ven, and Eisenhardt – to highlight developments in the conduct of process research since the mid and late 1980s, and to identify a set of pointers for the conduct of future process research.